A study of green supply chain management, green innovation and environmental performance among Malaysian manufacturing companies - Abu Seman, Noor Aslinda; Zakuan, Norhayati; Mat Saman, Muhamad Zameri; Md Ariff, Mohd Shoki; Sulaiman, Zuraidah (Research India Publications, 2015)
The growing of environmental concern from customers, buyers, communities, and government regulations has forced companies to implement Green Supply Chain Management (GSCM) practices and green innovation. GSCM practices and green innovation is believed to have strategic interconnection in improving environmental performance positively. Objective: This pilot study aims to identify the dominant practices of GSCM and green innovation that is implemented among Malaysian manufacturing companies and the correlation across them to environmental performance. Results: The pilot results reveal that some of GSCM practices and green innovation were found in this study to have direct impact on companies’ environmental performance. Conclusion: As a conclusion, manufacturing companies should focus considerable efforts and develop some innovation in order to deal with environmental issues along their supply chain.